The relationship between VAIC™, firm performance and firm value of companies: a cross-country analysis - Thomas, Bradley (Department of Finance and Tax, 2026)
Purpose – The aim of this research was to examine the relationship between intellectual capital (IC), firm performance and firm value in South Africa, Brazil and Indonesia. Design/Methodology/Approach – The study applied the difference generalised method of moments (DGMM) estimator to investigate the relationship between 787 listed firms from the Johannesburg Stock Exchange (JSE), the Brazil Stock Exchange (B3.S.A) and the Indonesia Stock Exchange (BEI), spanning 5 years from 2019–2023 making use of the VAIC™ approach and its components to test the relationship with firm performance and firm value. The study used secondary data from Eikon Refinitiv. Findings – The study found that firms in all three countries leverage both intangible and physical capital at a composite level (VAIC™) to enhance performance. However, from a valuation perspective, the market only reward firms in Brazil at an aggregate level. The individual VAIC™ components show mixed results across the countries. Brazilian and Indonesian enterprises appear to utilise their human and physical capital more efficiently to generate shareholder returns and create value compared to South African companies. In contrast, South African firms tend to invest in innovation—such as patents, trademarks, systems, and processes—to achieve positive returns, even though this may the stifle shareholder wealth creation. Practical Implications – In general, physical capital dominates the findings. It suggests that the market continues to reward firms for using this source of capital to generate shareholder wealth. The findings imply SCE and HCE offer limited value on their own and that it benefits firms to use both intangible and tangible assets. Originality/Value – The study builds on the research of Nadeem et al. (2017) and Nadeem et al. (2019) by providing an updated analysis utilising the DGMM. There is a dearth of studies that have adopted the DGMM to investigate the relationship of IC with firm performance and firm value on a cross-country basis on South Africa, Indonesia and Brazil. Given the limited research using this particular method of the GMM, we are contributing to filling this void.